Morphometric studies in the genus Clerodendrum L. - Deshmukh, S A; Chavan, S R; Gaikwad, D K (Current Botany, 2013)
Six Clerodendrum L. species from Kolhapur district were morphometrically analyzed with the help of PCA, cluster analysis and CD. It was observed that the quantitative characters viz. petiole length, leaf length and leaf width have great significance in delimitation of all the species and corolla tube length, leaf width, gynoecium length and leaf length have great contribution in separation of the taxa. Clerodendrum multiflorum (Burm.f.) O. Ktze.- Clerodendrum inerme (L.) Gaertn., Clerodendrum paniculatum L. - Clerodendrum viscosum Vent. and Clerodendrum inerme (L.) Gaertn. - Clerodendrum serratum (L.) Moon. are very closely related with each other and Clerodendrum multiflorum (Burm.f.) O.Ktze.- Clerodendrum paniculatum L. and Clerodendrum multiflorum (Burm.f.) O. Ktze. - Clerodendrum viscosum Vent. are significantly different from each other.